Casticin prevents DSS induced ulcerative colitis in mice through inhibitions of NF‐κB pathway and ROS signaling. (7th June 2018) - Ma, Jiamei; Yin, Ganghui; Lu, Zibin; Xie, Pei; Zhou, Hongling; Liu, Junshan; Yu, Linzhong
Abstract : Casticin, a compound purified from the Chinese herb Viticis Fructus, has been proven effective in preventing tumor progression in previous studies. Ulcerative colitis (UC) is a common inflammatory bowel disease that affects millions of people worldwide, but no effective and safe drugs are available. In this study, we aimed to study how did casticin affect UC by evaluating its effects on dextran sulfate sodium (DSS)‐induced colitis in mice. Our data suggested that casticin attenuated body weight loss, colon length shortening, and pathological damage in the colon of DSS‐treated mice. Casticin decreased reactive oxygen species level and chemocytokines (IL‐1β, IL‐6, TNF‐α) productions in colon tissue. The decreased reactive oxygen species level and suppressed proinflammatory cytokines productions were also confirmed in casticin‐treated LPS‐stimulated RAW264.7 cells and hydrogen peroxide‐treated CACO‐2 cells in vitro. Mechanistically, casticin treatment prevented the profound activation of AKT signaling caused by DSS administration. And casticin inhibited the productions of proinflammatory chemocytokines through downregulating AKT/NF‐κB pathway in macrophages. Meanwhile, data revealed that casticin increased expressions of endogenous antioxidants peroxiredoxin 3 and MnSOD were through activation in FOXO3α signaling by downregulating AKT signaling in colon epithelium cells. Our findings demonstrated that casticin alleviated DSS‐induced UC by increasing the antioxidant enzyme peroxiredoxin 3 and MnSOD expressions, and decreasing the production of proinflammatory chemocytokines through inhibition of AKT signaling.